PENGARUH NILAI TUKAR RUPIAH TERHADAP RETURN SAHAM DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING - Eka Pujawati, Putu; Wiksuana, I Gusti Bagus; Sri Artini, Luh Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME 04.NO.04.TAHUN 2015, 2015)
Returns and profitability is the target to be achieved by all companies. Many things affect the return of which is the exchange rate. The research is aiming to determine the effect of the exchange rate on stock returns in the stock exchanges of Indonesia hospitality industry with profitability as an intervening variable The population in this research are all the companies in the hospitality industry are listed in the Indonesia Stock Exchange during the period 2012-2013. The data is analyzed by path analysis (path analysis), supported by SPSS version 17.0 The results of this study shows  that: (1) exchange rate negative effect on the profitability of return while positive impact on return. (2) the effect of the exchange rate returns through greater profitability than the direct effect of exchange rate on return. Recommended for  future research to increase the variables that affect the return and also expand the sample to the research results could be better.
Keywords: exchange rate, profitability and stock returns